PI3K Pathway in NSCLC - Martínez Martí, Alex; Felip, Enriqueta (Frontiers in Oncology, 2012)
The phosphatidylinositol 3-kinases (PI3Ks) are members of a family of intracellular lipid kinases that phosphorylate the 3′-hydroxyl group of phosphatidylinositol and phosphoinositides. PI3K regulate signaling pathways for neoplasia, including cell proliferation, adhesion, survival, and motility. Different classes of PI3K have distinct roles in cellular signal transduction. PI3K pathway is activated by several different mechanisms in cancers, including, somatic mutation and gene amplification. In this review, we examine the literature addressing PI3K mutation status and gene amplification, with an emphasis on non-small cell lung cancer.